TINJAUAN RELIGI ATAS MANUSIA DAN LINGKUNGAN - Yedi Purwanto (Fakultas Seni Rupa dan Desain ITB, 2007)
Human as the God's most noble creature was appointed as the leader in the world. With his knowledge, man must understand his environment, and has a responsibility to take care of his living environment in line with Commandment of God in the Quran.